Management of Cakruk Pintar Community Library in Sleman District Yogyakarta - Hayati, Nurul; Sunarti, Vevi; Gusmanti, Reza (Universitas Negeri Semarang, 2021)
Management of Cakruk Pintar community library by using the management of the School Education program management. The purpose of this study was to determine: (1) program planning (2) program organization (3) program implementation (4) program supervision and (5) assessment of the Cakruk Pintar Community library program in Sleman Yogyakarta. This type of research is a qualitative descriptive study. The results showed 5 findings. First, the smart cakruk community library identifies the needs of the community in initiating program planning. Second, organizing the smart cakruk community library program is managed by professionals. Third, the implementation of the smart cakruk community library program went well. Fourth, the supervision of the community library program is in accordance with predetermined standards. Fifth, the assessment of the community library program is quite good with increasing enthusiasm of the community in participating in it.